Characterization of a novel lncRNA RP3-340N1.2 and its association with a miR-4650-5p/SHC1-related regulatory network in lung adenocarcinoma - Fang Chen; Yan Yan; Wenting Yang; Zhilin Li; Daying Wang; Jianqiao Huang; Chaozhou Wan; Tingting An; Li Tong; Maoxia Ran; Yaqiong Dong; Yunfen Chen (PLoS ONE, 2026)
Long noncoding RNAs (lncRNAs) are increasingly recognized as regulators of cancer-related biological processes. However, the functional significance of many lncRNAs in lung adenocarcinoma (LUAD) remains incompletely understood. In this study, we identified RP3-340N1.2 as an upregulated lncRNA in LUAD through analyses of public transcriptomic datasets, which was further confirmed by quantitative real-time PCR in LUAD cell lines. Functional assays demonstrated that knockdown of RP3-340N1.2 was associated with reduced proliferation, migration, invasion, and clonogenic growth of LUAD cells in vitro. In addition, suppression of RP3-340N1.2 attenuated tumor growth in a xenograft model. Bioinformatic analysis using the LncBase Experimental v3 database identified hsa-miR-4650-5p as a potential interacting microRNA of RP3-340N1.2. This interaction was further examined by dual-luciferase reporter and RNA immunoprecipitation assays. Functional experiments additionally showed that miR-4650-5p overexpression was associated with reduced proliferative and migratory capacities in LUAD cells. Among the predicted downstream targets of miR-4650-5p, SHC1 was selected for further investigation. Alterations in RP3-340N1.2 or miR-4650-5p expression were accompanied by corresponding changes in SHC1 expression and ERK1/2 phosphorylation. Furthermore, rescue experiments demonstrated that SHC1 knockdown largely reversed RP3-340N1.2-associated cellular phenotypes, supporting the functional involvement of SHC1 within this regulatory framework. Collectively, these findings indicate that RP3-340N1.2 is aberrantly expressed in LUAD and may participate in tumor-associated cellular behaviors through a miR-4650-5p/SHC1-related regulatory mechanism. This study provides preliminary evidence supporting the potential relevance of RP3-340N1.2 in LUAD and offers additional insight into lncRNA-associated regulatory networks in this disease.